Case Report: Nicotine Addiction-Adolescence obsession - Mira Yustika; Agung Ikhssani; Putu Ristyaning Ayu Sangging (Jurnal teknologi Kesehatan Borneo, 2021)
Nicotine dependence is a chronic relapse defined as a compulsive desire to use it, regardless of social consequences, loss of control over intake, and appearance of withdrawal symptoms. Nicotine dependence develops over time as a person continues to use nicotine. The most commonly used tobacco product is cigarettes, but any form of tobacco use and use of e-cigarettes can lead to dependence. Nicotine dependence is a serious public health problem because it causes continued tobacco use, which is one of the leading preventable causes of death worldwide, causing more than 8 million deaths per year. The result of the journal review is that preventing the use of tobacco products among adolescents is critical to ending nicotine addiction worldwide. The impact caused by nicotine tends to be bad, so stopping is the way out. Different levels of influence should be considered in interventions aimed at adolescent smokers, including psychological influences, addictions, peers and parents. This review article contains about the effect of nicotine on adolescents and what strategies can be done to stop the problem.